2020
DOI: 10.18632/oncotarget.27575
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pattern of one-carbon metabolism, a nutrient-sensitive pathway, in invasive breast cancer: A metabolomic study

Abstract: Altered cell metabolism is a hallmark of cancer and critical for its development. Particularly, activation of one-carbon metabolism in tumor cells can sustain oncogenesis while contributing to epigenetic changes and metabolic adaptation during tumor progression. We assessed whether increased one-carbon metabolism activity is a metabolic feature of invasive ductal carcinoma (IDC). Differences in the metabolic profile between biopsies from IDC (n = 47) and its adjacent tissue (n = 43) and between biopsies from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
2
1
0
Order By: Relevance
“…Some other findings of the current study have also been reported by previous literature . For instance, galactose metabolism is known to influence mitochondrial dysfunction and cancer growth in human BC cells and is also an early indicator of other gynecological cancers. Moreover, recent comparative studies have identified decreases in glycine, serine, and threonine to be indicative of the metastatic potential of EBC and subsequent risk of invasive ductal carcinoma . In the current study, the levels of all three metabolites were significantly reduced ( p < 0.05) in EBC patients (see Figure ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some other findings of the current study have also been reported by previous literature . For instance, galactose metabolism is known to influence mitochondrial dysfunction and cancer growth in human BC cells and is also an early indicator of other gynecological cancers. Moreover, recent comparative studies have identified decreases in glycine, serine, and threonine to be indicative of the metastatic potential of EBC and subsequent risk of invasive ductal carcinoma . In the current study, the levels of all three metabolites were significantly reduced ( p < 0.05) in EBC patients (see Figure ).…”
Section: Discussionsupporting
confidence: 87%
“…57−59 Moreover, recent comparative studies have identified decreases in glycine, serine, and threonine to be indicative of the metastatic potential of EBC 31 and subsequent risk of invasive ductal carcinoma. 60 In the current study, the levels of all three metabolites were significantly reduced (p < 0.05) in EBC patients (see Figure 4). Finally, our results show significant disturbances in glutamate and glutamine metabolism, a finding that is well-known in cancer research.…”
Section: ■ Discussionsupporting
confidence: 53%
“…Analysis of "scMetabolism" indicated that MuSCs from DMD mut muscles had higher activities of oxidative phosphorylation (OXPHOS), citric acid cycle (TCA cycle), glycolysis metabolism, and pentose phosphate pathway (PPP) activities compared to MuSCs from control muscles (Figure 6); (2) Purines and pyrimidines are fundamental building blocks of nucleotides, which are crucial for cell proliferation. Proliferative cells require nucleotides, including purines and pyrimidines for synthesizing cellular components [16]. When there is a dysregulation in purine and pyrimidine metabolism, there is an increase in DNA damage and cell turnover [17].…”
Section: Differential Metabolic Pathways Of Muscs Within Dmd Mut and ...mentioning
confidence: 99%
“…Nuclear magnetic resonance ( 1 H NMR) spectroscopy-based metabolomics method is one of the powerful analytical techniques employed to study the metabolic profile of a wide range of biological samples, such as serum, faecal and urine, which require only a minimal amount of samples [24,25] . Several published studies have proved the utility of metabolic profiles anaysed by 1 H NMR in the detection of breast cancer [26,27] . When analysing serum samples with 1 H NMR, Zhou et al [28] discovered that nine metabolites were substantially altered in breast cancer compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%